INTEGRATING ONLINE READING ACTIVITY IN A CRITICAL READING COURSE: A COURSE EVALUATION - Sri Kusuma Ningsih (University of Kuningan, 2022)
Advancement of information and communication technology (ICT) has promoted changes on students’ reading behavior; from conventional reading and online reading. In the current study, online reading activity was integrated in a critical reading course in an English department of a private university. In the course, fifty-eight EFL students were exposed with paper-based reading and online reading. After eight week, an evaluation was performed to the course. All participating students were surveyed and twelve of whom were interviewed. The quantitative data from the survey were analysed using Rasch Model while thematic analysis was performed to the qualitative data. Findings showed students’ preference to online reading activity than paper-based reading, particularly for those who were already familiar with electronic reading devices. Online reading was perceived to provide students with flexibility while reading and helped them navigate the reading sections at their ease. Small screen size and lights from the screen appeared to issue students’ eye irritation. Recommendation thus was offered particularly regarding further curriculum development that integrate online reading activity in a reading course.